AB0090 Discovery of Early Biomarkers Specific of Hip or Knee Osteoarthritis by Quantitative Proteomic Profiling of Human Articular Cartilage Degradation. (9th June 2015) - Ruiz-Romero, C.; Lourido, L.; Calamia, V.; Fernández-Puente, P.; Mateos, J.; Rocha, B.; Fernández-Costa, C.; Fernández-Lόpez, C.; Oreiro, N.; Blanco, F.J.
Abstract : Background: Osteoarthritis (OA) is characterized by the progressive loss of cartilage structural extracellular matrix (ECM) components. The release of these proteins from the tissue can vary according to the stage of the disease and the specific joint that is affected. Objectives: The aim of this study was to perform a quantitative proteomics approach to identify and quantify those proteins differentially released from healthy (N) and OA human articular cartilages from hip and knee. Methods: Tissue explants for the proteomic analysis were obtained from the dissection of cartilage from 4 femoral heads (2 N and 2 OA) and 4 tibial condyles (2 N and 2 OA). Among the OA samples, we differentiated the wounded zones (WZOA) from those corresponding to the area adjacent to the lesion, or unwounded zones (UZOA). Cartilage shavings from each donor were cut into 6 mm discs and three discs per donor were placed into 96-well plates and cultured during 6 days. The conditioned media from each condition (N, WZOA and UZOA) were collected and their proteins were digested with trypsin. The resulting peptides were labelled with different isobaric tags using the iTRAQ reagents (ABSciex). Then, labelled peptides from the different conditions were mixed, desalted and separated by liquid chromatography (LC). The resulting fractions were grouped and resolved by reversed-phase nano-LC coupled to mass spectrometry (MS). The identification and relative quantification of the proteins was carried out with Protein Pilot 3.0 software. Results: Globally we were able to identify with high confidence 234 unique proteins released from the cartilage explants. After statistical analysis, we found 76 proteins showing differences in abundance (0.55≤ ratio ≥1.8, p ≤0.05) between the different OA zones (WZOA and UZOA) and N samples from the different joints. A first group of proteins was quantitatively altered specifically in the conditioned media from UZOA samples (putative early OA biomarkers); a second group of proteins was only altered in WZOA samples (late OA biomarkers), and finally a third group was altered in both OA zones compared to normal (early and progression biomarkers). Most proteins showed a similar release profile in both hip and knee OA. However, some of them were differentially modulated depending on the joint of origin of the cartilage (Table 1 ), being putative joint-specific biomarker candidates either for early diagnosis of OA or progression studies. Among these, we confirmed the increased release of cartilage intermediate layer protein 1 (CILP1) specifically from hip cartilage by western blot analysis on independent samples (n=3). Furthermore, this specific modulation was also observed in hip cartilage by real-time PCR (n=3). Conclusions: In this work, we describe a novel panel of proteins differentially released from OA human articular cartilage. This altered release was joint-characteristic in ten cases, which are putative biomarker candidates for early hip or knee OA. The presence of these proteins is now being explored in biological fluids (synovial fluid and serum) for the development of early diagnosis and/or anti-OA therapy monitoring strategies. Disclosure of Interest: None declared